Konversi Kitin Menjadi Kitosan Dari Limbah Industri Ebi - Ongky Alexander; Ahmad Fadli; Drastinawati Drastinawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Chitin can be transformed into chitosan by deacetylation process using chemical methods. Chitosan many applied in various fields especially in the field of biomaterials. The purpose of this research to study the effect of the mass ratio of chitin and NaOH volume of the reaction time in the process of deacetylation. Shrimp shells in the puree with a size of 50 mesh. Chitin in shrimp shell powder are in isolation with process deproteination and demineralization. Chitin which has been synthesized and then transformed into chitosan by deacetylation process operating conditions with a temperature of 120oC, stirring speed of 150 rpm, the mass ratio of chitin and NaOH 50% volume 1:15, 1:20, 1:25 (w/v) and time reaction of 0.5; 1; 1.5; 2; 2.5 and 3 hours. The results showed that increasing the value of the mass ratio of chitin and NaOH volume of the reaction time resulting in increased degree of deacetylation and depreciation ash content and yield of chitosan, while the water content does not have a significant effect. On the addition of NaOH volume 15 , 20 and 25 ml , and the reaction time of 0.5 ; 1; 1.5; 2; 2,5; 3 hours have the value of yield, moisture content, ash content, degree of deacetylation and molecular weight respectively ranged from 86.6-63.5%, 1.21-1.00 %, 1.93-1.06 %, 67.52-86.09 % and 2,699 x109-2,9334 x109 g/mol.Keywords: deacetylation; demineralization; deproteination; chitin; chitosan;